A critical investigation of constraints in Nigerian inward logistics - Tewari, Rishica (2011)
As global trading intensifies, more and more businesses are finding cheaper and efficient ways to source raw materials and finished products. They have also started re-evaluating their business strategies and are relocating their manufacturing sectors to countries that provide abundant resources at low costs in the hope of attaining competitive advantage. Countries with emerging economies have recognised the opportunity and are directing their developments towards the overall infrastructure to accommodate the potential growth of demands for inward logistics. However, problems do come up during the process. The objective of this research was to gain an understanding of the role that the inward logistics played in international trade. The analysis was focused on developing countries, taking Nigeria as a case study. Logistics is divided into two, inbound (or inward) and outbound logistics. Inward logistics essentially means the when flow of goods, people or information is directed towards the interior. It encompasses transportation, warehousing, inventory management, production and procurement. Inward logistics has become a major source of competitive advantage and global trade has been responsible for its boosts. Previous researches have associated inward logistics to the production process. According to them, inward logistics is the flow of goods such as components, sub-assemblies and raw materials into the manufacturing plants. However, this research would bring in a new perception. Inward logistics does not only imply the flow of goods and information towards the manufacturing plant but can also be towards retailers, warehouses, distribution centres or even to the end consumers. To understand the process of inward logistic within a country, Picard’s 1983 and Schary and Skjett in 2001 model on global distribution is illustrated. Both the models focused on the role that the transportation played while bringing into a country and distributing it within the region. It involves freight forwarder or logistics provider, local transport and carrier. Nigeria is the 12th largest producer of oil which makes up 85% of the country’s exports and 95% of its revenue. However, despite this almost 50% of the population of the country remains poor. The transport infrastructure, since the 1970 remains fractured as a result of corruption at every level of the government. This is just one of the many countries with emerging economies that struggle to build and maintain an efficient logistics system. For the primary analysis, in depth interviews were conducted with the objective of obtaining an original piece of work on the constraints on inward logistics from a business perspective. The managers from the operations departments of five companies were taken for the analysis. These companies belong to the automobile, textile, agriculture and express delivery industry. The interview was split into two parts; the first was related to the processes of bringing in goods into the country using marine ports. In Nigeria, the standard importation process is followed except for few slight variations. It is required by law to have an account at a local bank which will be responsible for all the transactions taking place between the exporter and the receiver. Also, inspections agencies are used to inspect the documents and the goods being brought into the country to ensure safety and usability. These agencies differ according to the goods. Almost all the companies complained about the customs process and the procedure of clearing the goods. Due to corruption, delays were made intentionally with the excuse of either the presentation of wrong documents or wrong duty evaluation. Other issues included lack of container handling equipments, under developed links to the ports etc. The main cause for this problem is the deficient investment for its expansion and update. Up till now, no efforts have been made to address the issue. For some companies, about 7-8% profit margin would have to be kept for the purpose of informal payment in order to clear the goods quickly. The second part of the analysis focused on the companies’ distribution system and the issues they face when delivering the units within the country. Some of the problems highlighted were bad roads, highway robberies and non-unionisation of interstate custom documents. Companies have had to adapt to these situations. For example, all the companies have had to send armed escorts along with the consignments due to the high risks of theft. And while efforts are being made by the government to address the issues, they have been restrictive and inconsistent. To conclude, while it is essential for every country to have an efficient logistics, it can at times be quite difficult to reach up to that level and while certain rules and format set by the developed countries is related to achieving it, it cannot be applied to every country.